Identification and Quantification of Polycyclic Aromatic Hydrocarbons in Processed Chicken Meat Products - Muthukumar, M.; Banerjee, Rituparna; Naveena, B. M.; Sanganabhatla , Divya (Journal of Meat Science, 2019)
Experiments were carried out to identify and quantify the concentrations of polycyclic aromatic hydrocarbons (PAHs) in tandoor chick en, chicken tikka and smoked chicken and to evaluate the impact of different cooking methods on the levels of PAH compounds. The  PAH’s viz., Acenaphthylene, Acenaphthene, Fluorene, Phenanthrene, Anthracene, Fluoranthene, Pyrene, Chrysene, Benz (a) anthracene,  Benzo (k) fluoranthene, Benzo (b) fluoranthene, Benzo (a) pyrene, Indeno (1,2,3-cd) pyrene, Dibenzo (a,h) anthracene, Benzo (g,h,i)  perylene were separated and quantified using GC-MS. The calibration curves for 15 different compounds of PAHs at various concen trations were found to be linear with standard regression value. Test results showed that all the PAH compounds were below the limit of  quantification in chicken tikka samples. However, 2 out 3 tandoor chicken samples showed presence of pyrene at 0.01 ppm level. Smoked  chicken samples also showed the presence of pyrene and anthracene at 0.01 to 0.02 ppm level. None of the products showed the  presence of carcinogenic PAH compounds viz., benzo[a]anthracene, benzo[b]fluoranthene, chrysene, and benzo[a]pyrene. Analysis of  seekh kebabs cooked under different cooking methods for PAH indicated that, the levels were below the limit of quantitation (0.01mg/ kg). Current study indicates that, the level of carcinogenic PAH compounds are below the detection level in routinley consumed meat  products, however, more samples need to be screened.
Keywords: Meat Products; Cooking Methods; PAH Compounds; GC-MS MS